Identificação e atividade enzimática de Aspergillus seção Aspergillus oriundos de presunto cru ovino para uso como cultura iniciadora - Magrini, Lísia Nicoloso (2024)
Fungi contribute to the development of unique flavors, aromas, and textures during food processing through the production of enzymes, especially proteases and lipases. Thus, the focus of the study was the molecular identification and characterization of the enzymatic profile of 22 fungi of the genus Aspergillus, section Aspergillus, isolated from matured sheep hams. Molecular identification was performed through single-spore isolation, cultivation, DNA extraction and purification, followed by amplification via PCR and sequencing of regions of the calmodulin and beta-tubulin genes. The sequences obtained were analyzed and compared with reference isolates available in GenBank. The following species were identified from the analyzed material: A. aurantiacoflavus (n=1), A. chevalieri (n=4), A. montevidensis (n=4), A. proliferans (n=2), A. pseudoglaucus (n=5), and A. ruber (n=6). These isolates were tested for the production of lipases in solid culture media based on Tween 20 (lauric acid ester) and Tween 80 (oleic acid ester), and proteases in milk medium. Enzymatic activity was determined by the formation of halos around the colonies, which were classified as low, moderate or intense, depending on their extent. The lipolytic activity of all species evaluated was more prominent against lauric acid ester when compared to oleic acid ester, with an increase in activity after 14 days of culture. Proteolytic activity was only observed in strains of A. aurantiacoflavus, A. montevidensis, and A. proliferans, and it was weak and only appeared after 14 days. Literature review indicates that there are no real mycotoxins produced by A. aurantiacoflavus, A. chevalieri, A. montevidensis, A. proliferans, A. pseudoglaucus and A. ruber. Therefore, the species evaluated are technologically promising for use as starter cultures for the maturation of sheep hams, however additional sensory evaluations are necessary.